Impact of XPD Lys751Gln Genetic Polymorphism on Oxaliplatin-Based Regimen Induced Toxicities in Iraqi Colorectal Cancer Patients - Muthanna, Rand; Eman Saadi Saleh; Zuhair Alsammarraie, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2025)
The XPD Lys751Gln polymorphism may affect individual differences in DNA repair ability, which could increase a person's risk of developing toxicity when receiving oxaliplatin containing regimen in colorectal cancer patients. Therefore, assessment of XPD Lys751Gln polymorphism may generate crucial data for identifying individuals at high risk for serious adverse effects and thus choosing the best treatment option. Hence the aim of current research is to find out the association between XPD Lys751Gln polymorphism and oxaliplatin based regimen toxicities among sample of Iraqi population. 72 CRC who are on oxaliplatin based regimen were enrolled in the study and were followed for 4 cycles. Polymerase chain reaction (PCR) was used for genotyping, followed by sequencing. Toxicities were recorded before the start of each of the four cycles then the relationship between genetic polymorphism and observed toxicities were examined. There was no significant association between Lysn751 Gln genotypes and studied hematological and non-hematological toxicities. Taken together, The XPD Lys751Gln polymorphism cannot be considered a potential biomarker for platinum induced toxicity.